The Influence of Adding Glycerol and Spirulina on The Characteristics of Starch-Based Bioplastics Film from Potato Peel Waste - Kamilah Pathun Ni'mah; Muhammad Fahmi Hakim; Leggy Doriyanti Julia Putri; Fira Rahmawati (Hydrogen: Jurnal Kependidikan Kimia, 2023)
The development of bioplastic films is one of the efforts to reduce plastic waste. The polymer used as the basic material for making bioplastic films is starch. Potato peel waste can be repurposed by extracting its starch content. This research has the purpose to investigate the influence of adding glycerol and spirulina on the characteristics of bioplastic films made from potato peel starch, and to ascertain the optimum composition of raw materials. Bioplastics were produced by casting method from potato peel starch with variations of glycerol and spirulina. The bioplastic composition in this research includes K0 (0 ml glycerol and 0 grams spirulina), K1 (2.5 ml glycerol and 0.3 grams spirulina), K2 (1.25 ml glycerol and 0.3 grams spirulina), K3 (2.5 ml glycerol and 0.15 grams spirulina), and K4 (1.25 ml glycerol and 0.15 grams spirulina). The characteristics of bioplastic films include thickness testing, tensile strength, elongation at break, and degradation. The results from the characterization of bioplastic films indicate that the addition of glycerol and spirulina is inversely proportional to the tensile strength produced, meaning it decreases. However, the addition of glycerol and spirulina is directly proportional to the percentage of elongation produced, meaning it increases. The addition of spirulina has an impact on the degradation time of bioplastic films. The optimal raw material ratio in this research is found in sample K4, with a tensile strength value of 23.038 MPa, elongation at break of 4.385%, thickness of 0.1367 mm, and complete degradation occurring on the sixth day.